A young man with persistent dyspepsia: the unexpected virtue of proton-pump inhibitors - Fraticelli, Paolo; Mattioli, Massimo; Benfaremo, Devis; Biondi, Lorenzo; Cardinali, Marco; Gabrielli, Armando (Acta Biomedica Atenei Parmensis, 2019)
A 26-year-old man was referred to our department for a 3-year history of dyspepsia responsive to oral pump-inhibitors therapy. During the last year, he underwent a gastroscopy, a colonoscopy and a computed tomography enterography that failed to reveal an underlying organic disease: a diagnosis of functional dyspepsia was made. Because of the persistence of symptoms, he came to our ambulatory where we performed an abdominal ultrasound that revealed the presence of multiple bi-lobar lesions of the liver suspected for metastases and a hypoechoic solid lesion of the pancreas body, confirmed by a contrast enhanced computed tomography. Laboratory tests showed high chromogranin A and gastrin level, and a liver biopsy was consistent with a metastatic pancreatic neuroendocrine tumor. This report aims to underlie the diffuse heterogeneous diagnostic management of some common gastrointestinal symptoms, such as dyspepsia, that are too often approached with the prescription of proton pump inhibitors.